1921
DOI: 10.1021/ja01436a025
|View full text |Cite
|
Sign up to set email alerts
|

THE RÖLE OF MERCURIC NITRATE IN THE “CATALYZED” NITRATION OF AROMATIC SUBSTANCES.4 [FIRST PAPER.]

Abstract: the same two stages really exist, but that iron catalyzes the secondary reaction so that it is practically instantaneous. Reactions.It has long been known that perchloro-mercaptan can be reduced by silver dust,1 iron and acetic acid,2 or stannous chloride, or tin and hydrochloric acid3 to thiophosgene, according to the reaction CSCI4 + SnCl2 -CSC12 + SnCl4. When this reduction was tried with zinc and hydrochloric acid the perchloro-methyl-mercaptan disappeared completely; apparently it was reduced to methane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1948
1948
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Abbreviations: DNP = 2,4-dinitrophenol; NB = nitrobenzene; DNB = crude dinitrobenzene. 6 The major portion of this fraction was 2,4,2',4'-tetranitrodiphenylamine.…”
Section: T H Imentioning
confidence: 97%
“…Abbreviations: DNP = 2,4-dinitrophenol; NB = nitrobenzene; DNB = crude dinitrobenzene. 6 The major portion of this fraction was 2,4,2',4'-tetranitrodiphenylamine.…”
Section: T H Imentioning
confidence: 97%
“…Early workers reported that the yield of nitrobenzene approached 50% when the oxynitration reaction was carried out in concentrated nitric acid. 5 Tsutsumi and Iwata and Osawa and his co-workers studied the effects of other metal oxides and metal nitrates on nitration with nitric acid.6™8 However, only mercuric oxide and mercuric nitrate accelerated the reaction importantly and altered the isomer distribution.6'7•9 Komoto and his associates examined the mercuric acetate catalyzed nitration of toluene using concentrated nitric acid in acetic acid at 80 °C.10 Under these conditions, the catalyzed reaction produced the isomeric nitrotoluenes in good yield. Several investigators have proposed that electrophilic aromatic mercuration is the first step in this reaction.7•10 The nature of the subsequent steps in the process remains unclear.…”
mentioning
confidence: 99%
“…It was also reported that the same oxynitration: takes place with benzoic acid (80). Accounts, more or less complete, are available of work on this reaction in several countries during the period 1914 to 1918 (3,6,7,9,10,11,19,20,22,23,24,26) and shortly thereafter (4,13,32). Blechta and Patek (4) have extended the oxynitration reaction to toluene, and Davis (9) to naphthalene.…”
mentioning
confidence: 99%